Evaluation of Chronic Dietary Risk of Trifloxystrobin and Bupirimate in Cucumber Based on Supervised Residue Test - Yanli Qi; Weirong Wang; Pengcheng Ren; Shu Qin; Jindong Li; Junli Cao (Foods)
Trifloxystrobin and bupirimate are widely used as fungicides for controlling powdery mildew in cucumber cultivation. Supervised field trials were conducted in 12 representative regions across China, following Good Agricultural Practices (GAP) guidelines, to investigate their residue patterns and potential dietary exposure risks. Cucumber samples were analyzed using a validated method involving extraction with acidified acetonitrile (2% acetic acid, v/v), cleanup with primary secondary amine (PSA) and graphitised carbon black (GCB), and quantification by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). The method demonstrated excellent recovery rates (85–103%) throughout four spiking levels (0.01, 0.1, 0.3, and 1 mg/kg), with relative standard deviations (RSD) ≤ 4.8%. At 3 days after treatment, the residues of trifloxystrobin (including trifloxystrobin acid), bupirimate, and ethirimol in cucumbers were found to range from <0.01 to 0.013 mg/kg, <0.01 to 0.076 mg/kg, and <0.01 to 0.04 mg/kg, respectively. A chronic dietary risk assessment was conducted using a probabilistic model. The results showed an acceptable chronic risk (RQc ≤ 2.476%) for trifloxystrobin, bupirimate, and ethirimol across different sexes and ages, supporting the conclusion that the use of these fungicides in cucumber cultivation under the tested conditions was safe for Chinese consumers. More research was needed on children because they are at higher risk than other groups.